Discursos sobre o universo do trabalho e da tecnologia no romance Usina, de José Lins do Rego - Ribeiro, Vanessa Lopes (2015)
This thesis consists of a dialogical analysis of the discursive constructions regarding the labor and technology universe in the novel "Sugar Mill" by José Lins do Rego, published in 1936. To conduct the proposed analysis, this research is based on the theoretical assumptions of Mikhail Bakhtin and the circle, language scholars, for whom the novel is a great statement which is born from a social-interactive space. On this same dialogical perspective, in relation to the labor and technology universe, this study seeks reflections of important thinkers, such as: Marx, Engels, Lafargue, Lukács, Sennett and Heidegger. The composition of the discourse presented in this study is structured from the selection of these authors and others, present, mostly in the syllabus of the disciplines of the Postgraduate in Technology Program (PPGTE), more specifically, in the Research Project "The discursive formalization of work and technology universe in Brazilian literary texts" that binds this thesis. The discursive constructions about work and technology are investigated from a circuit of voices present in the novel. This circuit of voices strengthens the key idea, critical synthesis of the author, his reflection on the working life on the plantations and the sugar mills, which in the ingenuity years there were more humane relations between people and between them and nature, pointing to a work as greater socialization factor, thus. The architectural of the novel is constituted by a statement which is established by the repetition of this thesis, guaranteed by the circuit of voices. This multiplicity of voices, represented by the characters and the narrator, is organized by the author so that the tone of the narrative evidences the anthropomorphization of the sugar mill. In resistance to this discourse of technological determinism, in the symbolic field, the author makes use of other discourses, such as the Christian tradition, the voice of the characters, D. Dondon, the sugar mill owner's wife, aggregates and workers from the ingenuity years, to make his thesis prevail. For this reason, the author organizes the narrative events so that the enunciation plan is evident to the reader in two moments: the rise and the decline of modern machinery at the Bom Jesus mill. In the first moment, with the modernization of the machinery of the mill which symbolizes the rise of this system, that is, working under the precepts of capitalism, the nature starts to crumble and human relations and of man with nature become less humanized in a sense of estranged labor. In the second, with business failure at the Bom Jesus sugar mill, the author signals for a humanization process in which, above all, the nature presents in a personified way, as a punitive response to human ambition.